Improvement in the Reinforced Concrete Beam with Embedded Polystyrene under Static Load - Lim Yong Tat; Jen Hua Ling; How Teck Sia; Leong Wen Kam; Joseph Toh Sheng Ngu (Faculty of Engineering and Technology, Sampoerna University, 2023)
Reinforced concrete beam is normally used as a skeletal frame to withstand the loads on the building. However, a long-span beam requires a larger beam section due to the concerns of excessive deflection and failure. Under such circumstances, a large portion of beam strength is used to sustain its own weight which is uneconomical. This problem could be overcome by reducing some portions of concrete using lightweight materials like polystyrene. The replacement should technically be applied without affecting the structural performance of the beam. This study aimed to develop an optimum design of lightweight beam by incorporating polystyrene in the conventional reinforced concrete beam. The specimens were tested with a static load using the four-point load test in order to investigate the behaviour of the beam. The effects of the parameters, such as the spacing of the polystyrene, and the amount of reinforcements were observed. The performance of the beams was evaluated in terms of the ultimate load, strength to weight ratio (s-w ratio), ductility, and failure mechanism. The results show that the lightweight beam, with 11.8% concrete replacement, outperformed the conventional beam by 47% to 61%, in terms of the s-w ratio.